2018
DOI: 10.3390/molecules23010201
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal TriCurin, A Synergistic Combination of Curcumin, Epicatechin Gallate and Resveratrol, Repolarizes Tumor-Associated Microglia/Macrophages, and Eliminates Glioblastoma (GBM) and GBM Stem Cells

Abstract: Glioblastoma (GBM) is a deadly brain tumor with a current mean survival of 12–15 months. Despite being a potent anti-cancer agent, the turmeric ingredient curcumin (C) has limited anti-tumor efficacy in vivo due to its low bioavailability. We have reported earlier a strategy involving the use two other polyphenols, epicatechin gallate (E) from green tea and resveratrol (R) from red grapes at a unique, synergistic molar ratio with C (C:E:R: 4:1:12.5, termed TriCurin) to achieve superior potency against HPV+ tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 62 publications
2
97
1
Order By: Relevance
“…Moreover, we also observed that the treatment of C6 cells with apigenin induced the activation and chemotaxis of microglial cells towards the glioma, restoring the microglia antitumor immune response to M1. In a similar study, Mukherjee et al () used flavonoids to treated mice with glioblastoma cells and repolarized M2‐ like tumor associated with microglia cells to the tumoricidal M1 phenotype and intra glioblastoma recruitment of natural killer cells. Quantitative analysis of chemotaxis assays showed a significant and dose‐dependent increase in microglial migration towards C6 cultures treated with apigenin compared with the controls, indicating the property of apigenin to recruit microglia cells with M1 profile to the tumor area and similar results observed with flavonoids rutin and quercetin (da Silva et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we also observed that the treatment of C6 cells with apigenin induced the activation and chemotaxis of microglial cells towards the glioma, restoring the microglia antitumor immune response to M1. In a similar study, Mukherjee et al () used flavonoids to treated mice with glioblastoma cells and repolarized M2‐ like tumor associated with microglia cells to the tumoricidal M1 phenotype and intra glioblastoma recruitment of natural killer cells. Quantitative analysis of chemotaxis assays showed a significant and dose‐dependent increase in microglial migration towards C6 cultures treated with apigenin compared with the controls, indicating the property of apigenin to recruit microglia cells with M1 profile to the tumor area and similar results observed with flavonoids rutin and quercetin (da Silva et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, S-phase cell cycle arrest, activation of caspases 3/7, and higher production of reactive oxygen species were demonstrated in vitro [130]. Sallem et al [131] have designed a new nanovector system for the delivery of a synthetic derivative of the RES molecule to the brain tissue, based on superparamagnetic iron oxide nanoparticles. This nanohybrid did not affect the mitochondrial metabolism, but damaged the plasma membrane of C6 glioma cells in vitro, indicating cytotoxic effects.…”
Section: The Effect Of Various Routes Of Administrationmentioning
confidence: 99%
“…Subsequently, M1 TAMs induced STAT1 and NF-κB (p65) expression, subsequently increasing the expression levels of IL-12 and thereby activating NK cells and CTLs, resulting in cytotoxicity (107). The same mechanism of action was also demonstrated in malignant glioma (108,109).…”
Section: The Role Of Curcumin In Tumor Immunomodulationmentioning
confidence: 84%